Effect on rates of breast feeding of training for the Baby Friendly Hospital Initiative. Issue 7325 (8th December 2001) - Cattaneo, Adriano; Buzzetti, Roberto
Abstract: Problem: Breastfeeding rates and related hospital practices need improvement in Italy and elsewhere. Training of staff is necessary, but its effectiveness needs assessment. Context: Eight hospitals in different regions of Italy. Design: Controlled, non-randomised study. Data collected in three phases. Training after the first phase in group 1 hospitals and after the second phase in group 2. Strategies for change: Training of trainers and subsequent training of health workers with a slightly adapted version of the 18 hour Unicef course on breastfeeding management and promotion. Key measures for improvement: Hospital practices, knowledge of 571 health workers, and breastfeeding rates at discharge, three, and six months in 2669 mother and baby pairs. Effects of change: After training hospitals improved their compliance with the "ten steps to successful breast feeding, " from an average of 2.4 steps at phase one to 7.7 at phase three. Knowledge scores of health professionals increased from 0.41 to 0.72 in group 1 (training after phase one) and from 0.53 to 0.75 in group 2 (after phase two). The rate of exclusive breast feeding at discharge increased significantly after training: 41% to 77% in group 1 and 23% to 73% in group 2, as did the rates of full (exclusive plus predominant) breast feeding at three months (37% to 50% in group 1 v 40% to 59% in group 2) and any breast feeding at six months (43% to 62% in group 1 v 41% to 64% in group 2). Lessons learnt: Training for at least three days with a course including practical sessions and counselling skills is effective in changing hospital practices, knowledge of health workers, and breastfeeding rates.